Value of Computer Software for Assisting Sonographers in the Diagnosis of Thyroid Imaging Reporting and Data System Grade 3 and 4 Thyroid Space‐Occupying Lesions. (25th June 2019) - Lu, Yuanyuan; Shi, Xian Quan; Zhao, Xiaohui; Song, Danfei; Li, Junlai
Abstract : Objectives: To analyze the ability of thyroid ultrasound computer‐aided diagnosis (CAD) detection software (AmCAD‐UT; AmCAD BioMed Corporation, Taipei, Taiwan) to assist sonographers in diagnosing Thyroid Imaging Reporting and Data System grade 3 and 4 space‐occupying lesions and to provide evidence for ultrasound doctors (UDs) to use the diagnostic recommendations of the AmCAD system to inform clinical decisions. Methods: In group 1, a retrospective study was performed on 234 cases of thyroid lesions confirmed by surgical pathology. The sensitivities, specificities, and accuracies of the diagnoses determined by the same UD independent of the software (UD) and after consulting the CAD software (UD + CAD) and by the software alone (CAD) were compared. In group 2, a prospective study was performed on 220 individuals with thyroid space‐occupying lesions recommended by physicians from our hospital to undergo needle biopsy to confirm the diagnosis. Ultrasound images were imported into AmCAD, and recommendations for needle biopsy or periodic follow‐up were obtained. According to the pathologic results of needle biopsy, consistency and coincidence rates of diagnostic recommendations for AmCAD were obtained. Results: In group 1, CAD and UD + CAD diagnoses achieved significantly higher sensitivities and accuracies of diagnosis than did independent diagnosis by the UD ( P < .05). In group 2, the software showed an overall intraclass correlation (κ = 0.786) and a diagnosis coincidence rate of 93.6% with needle biopsy results. Conclusions: AmCAD‐UT Detection improved the ability of UDs to diagnose Thyroid Imaging Reporting and Data System grade 3 and 4 space‐occupying lesions. Diagnostic recommendations of AmCAD are relatively consistent with needle biopsy results and can reduce the rate of unnecessary diagnostic needle biopsies.